Development of trigonometry module based on PBL that oriented to high school students' concept of understanding - Bazuri, Ahmad; Arliani, Elly (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2022)
This study aims to produce a problem-based learning module on trigonometry oriented towards the ability to understand concepts for grade X high school students and to describe the quality of the validity, practicality, and effectiveness of the module. This is a research and development with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The implementation of product development was conducted at the State Senior High School 1 Magelang, involving 36 students from class X MIPA 2. This research resulted in a trigonometry module based on problem-based learning syntax. The module is declared valid with an average assessment of experts' content of 4.24 (valid) and media experts of 4.45 (valid). The module was said to be practical, with the average student response questionnaire result of 3.93 (sufficient), the teacher's response questionnaire of 4.00 (practical), and the percentage of learning implementation of 95.24. With Minimum Completeness Criteria of 70, the module is declared effective with an average score of 80.72 for students' concept understanding, which is high, and the percentage of completeness is 87.88, which is good. Based upon the hypothesis test with a significance level of 0.05, it shows that the average understanding of students' concepts is more than 70.